Study on Seed Setting Performance of Selected Cluster Onion (Allium Cepa L.) Cultivars Under Vernalization And Non- Vernalization Conditions - Aradana, M.; Arasakesary, S.J.; Thirukkumaran, G. (Faculty of Agriculture, Eastern University Sri Lanka, 2023)
Cluster onion is popular among the growers of northern province and preferred by consumers throughout the state for its size, storability and palatability. This research presents an overview of the study of floral biology associated with cluster onion germplasms to improve cluster onion seed setting for hybridization. This was conducted at Regional Agricultural Research and Development Centre, Killinochchi using a Factorial Randomized Complete Block Design with three replicates. One standard variety (MICLO 1) with four selected cultivars (TVM 1, TVM 6, MH 4 & Kundu vallarai) of red onion were used. Five cultivars of onion with different methods taken as treatments viz, vernalization and non – vernalization. The research period from March 2022 to May 2022 to evaluate the floral behavior and hybridization of different onion germplasms under rainfed and irrigation conditions in Dry zone. Observations were analyzed in ANOVA using SAS software. This study shows that the vernalization process had a substantial impact on floral behavior and was helpful for the developing hybridization program. Significant differences were found between the vernalization and non-vernalization conditions. Overall, the study found that vernalization improves flowering ability, flower presence in umbels, umbel size, and seed quantity and quality. The most flowering onions were MH4 and MICLO 1 showed the highest number of flower count, umbel diameter, flower stalk and flower stalk width. TVM 6 and TVM 1 showed the intermediate responses with two treatments. But during the research period TVM 1 was most affected by fungal attack and the TVM 6 was field tolerant to major fungal disease and Kundu vallarai had the lowest responses with these two treatments because of this non-flowering ability.
Keywords: Cluster onion; Cultivar; Floral biology; Germplasm; Vernalization